Support for art interventions in children's hospitals and design strategies for alleviating negative emotions - Wang, Lianyu; Zheng, Dong (Frontiers in Pediatrics, 2026)
IssueChildren experience heightened negative emotions during healthcare visits. Art represents an effective non-pharmacological intervention, but its potential remains underutilized in Chinese children's hospitals.ObjectiveTo alleviate children's negative emotions, enhance the artistic quality of hospital spaces, and support the development of humanized, child-friendly medical environments.MethodsA mixed-methods approach was employed to investigate the spatial environments of two children's hospitals in Shanghai, China. Pediatric patients aged 3–14 years and their parents were studied using on-site surveys, questionnaire investigations, and naturalistic observation.ResultsSupport for art intervention was reported by 95.89% of children and 97.75% of parents. Existing artworks showed limited effectiveness, with 20.55% of children not noticing them and only 9.59% rating them as highly aesthetic. The blood-drawing and infusion areas elicited the strongest negative emotional responses, whereas the courtyard space was associated with the lowest levels of negative affect. For art preferences and activity demands in the infusion area, 193 valid questionnaires were collected. Analysis identified four Must-be (M) attributes, three One-dimensional (O) attributes, five Attractive (A) attributes, three Indifferent (I) attributes, and one Reverse (R) attribute, with no dubious attributes detected.ConclusionThis study provides empirical support for integrating art into children's hospital environments and proposes targeted art design strategies for pediatric infusion areas. The findings offer practical guidance for improving children's medical experiences and advancing the development of child-friendly healthcare spaces.